Modified Endoscopic Submucosal Dissection—An Alternative Modality for the Treatment of Sporadic Duodenal Papillary Adenomas - Zelong Han; Qingyuan Li; Chanelle Yeh Chua; Zhenjiang Wang; Jun Zhong; Ying Huang; Shaohui Huang; Aimin Li; Side Liu; Xiaobei Luo (Gastroenterology Research and Practice)
Conclusions: From our preliminary experience, ESD is a promising alternative in the treatment of superficial duodenal PAs; however, further investigation is needed.